Ethical Rule Breaking by Employees: A Test of Social Bonding Theory - Sims, Randi L. (Journal of business ethics, 2002)
As employees continue to lie, cheat, and steal from their employers, researchers have tried to help managers understand and possibly predict such deviant behavior. This study considers the specific employee misconduct of ethical rule breaking. Hirschi (1969) suggested that deviant behavior can be better understood by social bonding theory. The social bonding model includes four elements; attachment, commitment, involvement, and belief. It is proposed that Hirschi's social bonding theory can be used to understand ethical rule breaking by employees. Using a sample of 200 employees, the results indicate that the social bonding elements of attachment and involvement can be used to better understand the reported likelihood of ethical rule breaking of employees. Recommendations for better applying the social bonding model to ethical rule breaking are suggested.